2009
DOI: 10.1136/gut.2009.184556
|View full text |Cite
|
Sign up to set email alerts
|

Targeting delivery of anti-TNF  oligonucleotide into activated colonic macrophages protects against experimental colitis

Abstract: It is the first time a non-viral gene vector has been combined with an ASO targeted to activated macrophages in the treatment of CD. The inhibition of TNFalpha by this strategy represents a promising therapeutic approach for the treatment of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 34 publications
(26 reference statements)
1
47
1
Order By: Relevance
“…Therefore, intestinal epithelial cell-based therapeutics are a crucial field of interest for therapy. While previous studies showed a beneficial effect of targeting macrophages with siRNA [61][62][63][64] in our study, we demonstrated that intestinal epithelial cells can be a therapeutic target. Intestinal epithelial cells take up CaP/ PLGA nanoparticles in vitro and in vivo.…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, intestinal epithelial cell-based therapeutics are a crucial field of interest for therapy. While previous studies showed a beneficial effect of targeting macrophages with siRNA [61][62][63][64] in our study, we demonstrated that intestinal epithelial cells can be a therapeutic target. Intestinal epithelial cells take up CaP/ PLGA nanoparticles in vitro and in vivo.…”
Section: Discussioncontrasting
confidence: 70%
“…A more ideal way is to treat the IBD promoting TNF-a in the pathologically functional cells -colonic macrophages. Our previous study suggested that directly intracolonic delivering TNF-a ASO targeting colonic macrophage had significant therapeutic effects on experimental colitis and little influences on the physiological function of the immune system [17]. However, the inconvenience and suffering of enema brought to the patients and the complexity of the operation is a limiting obstacle to its further application.…”
Section: Discussionmentioning
confidence: 99%
“…However, NF-κB activation can also be pathologic; prolonged activation of NF-κB can result in the over-production of inflammatory cytokines like TNF-α (Li and Verma, 2002;Neish, 2004). TNF-α is an integral component of the mucosal immune response to intestinal pathogens, but when produced in excess leads to tissue-damaging colitis (Zuo et al, 2010). This is evident in laboratory animals with experimental colitis, as well as human patients with inflammatory bowel disease (Kaser et al, 2010;Zuo et al, 2010).…”
Section: Function Of the Intestinal Microbiotamentioning
confidence: 97%